Assessing the impact of the COVID-19 pandemic on adolescent pregnancy in Southwestern Uganda: a qualitative analysis using the socio-ecological model - Sophie E. Lyon; Elizabeth Kemigisha; Rupa Ramachandran; Shakillah Namatovu; Dorcus Achen; Daniel Atwine; Olena Ivanova; Viola N. Nyakato (Reproductive Health, 2025)
Adolescent childbearing remains a major public health challenge in Uganda. This study explores the impact of the COVID-19 pandemic on teenage pregnancy. This qualitative study, using a case study approach, conducted interviews with stakeholders affected by or involved with the prevention of adolescent pregnancy, such as young girls, their partners, their parents or caregivers, community health workers, and other community leaders. Data collection took place in 4 districts in Southwestern Uganda between March and June 2023. A total of 103 participants took part in 14 focus group discussions (FGDs) and we additionally conducted 28 individual in-depth interviews (IDIs). A codebook guided by a socio-ecological model focusing on individual, interpersonal, community and organizational, and policy factors that contribute to teenage pregnancy was developed for collaborative thematic analysis. Themes on the impact of COVID-19 on teenage pregnancy at the individual and interpersonal level included transactional sex, fear of COVID-19, and unsavory peer relationships. Community and organizational level factors included poverty, unsafe physical environments, limited access to SRH information and services, and lack of access to education. Policy level factors included ineffective political systems and procedures, encompassing restrictive lockdown policies and limited legal redress of violence against adolescent girls. Our results indicate that the global pandemic exacerbated many pre-existing risk factors of adolescent pregnancy across the community and organizational, interpersonal, and individual levels, most notably including increased poverty and limited education. New strategies are needed to bolster protective factors at the organizational and community levels to mitigate the risks associated with adolescent pregnancy. Keywords Adolescent pregnancy, Early childbearing, Risk fa
Keywords: Adolescent pregnancy; Early childbearing; Risk factors; Sub-Saharan Africa; Socioecological model; COVID 19; Pandemic